ALIGNING MARKET DEMAND AND LOCAL SUPPLY IN AGRO-EDU-TOURISM BUSINESS DEVELOPMENT IN EAST HALMAHERA, INDONESIA - Khairiyah Kamilah; Fandawa Saputra; Fatin F.S. Syukur; M. Muhajir Hasibuan (PEOPLE: International Journal of Social Sciences, 2026)
This study explores the strategic development potential of agro-edu-tourism in East Halmahera, Indonesia, through a case study of Kebun Tani Harmoni. Rural agricultural communities frequently face structural economic challenges, including income instability and limited value-added opportunities. Agro-edu-tourism offers an alternative development pathway by integrating agriculture, education, culture, and experiential tourism to strengthen local resilience and diversify livelihoods. Using a qualitative descriptive approach supported by quantitative data, this research combines visitor questionnaires, field observations, and stakeholder document analysis to evaluate the destination’s readiness to develop the business and alignment between local supply and market demand. The findings reveal strong potential derived from biodiversity, ethnobotanical knowledge, traditional agriculture, gastronomy, and living cultural heritage, which together create authentic educational tourism experiences. Community cohesion and local participation further strengthen the feasibility of community-based tourism development. However, several challenges remain, including limited tourism infrastructure, accessibility constraints, weak destination branding, and insufficient hospitality and digital marketing skills. The study identifies niche market opportunities among educational institutions, eco-tourists, cultural travelers, and CSR-based programs seeking meaningful and sustainable experiences rather than mass tourism products.This research proposes a phased and market-oriented development strategy emphasizing capacity building, participatory governance, modular infrastructure improvement, and collaborative partnerships. The study contributes practical insights into how rural communities can transform local cultural and agricultural assets into sustainable experiential tourism products while preserving authenticity and community ownership. The findings also provide implications for policymakers and tourism practitioners seeking inclusive and sustainable rural development models in emerging destinations.